2017
DOI: 10.1080/13685538.2017.1358258
|View full text |Cite
|
Sign up to set email alerts
|

Patient-perceived effectiveness and impact on quality of life of solifenacin in combination with an α-blocker in men with overactive bladder in Sweden: a non-interventional study

Abstract: Treating male lower urinary tract symptoms (LUTS) by targeting the prostate would have limited effect on overactive bladder (OAB) symptoms. This study assessed perceived symptoms and quality of life (QoL) of male patients with OAB treated with an α-blocker plus solifenacin in daily clinical practice. Male patients aged ≥40 years were included after the decision was made to initiate treatment with an α-blocker for LUTS plus solifenacin for OAB symptoms. The primary endpoint was change in patient perception of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…Альфаадреноблокаторы показали свою эффективность в различных аспектах коррекции нейрогенных расстройств мочевого пузыря. Так, в определенных клинических ситуациях терапия адреноблокаторами может привести к таким результатам, как уменьшение степени пузырномочеточникового рефлюкса (ПМР), улучшение со стороны императивного недержания, более редкие обострения инфекций мочевыводящих путей, выраженное улучшение уродинамических показателей, уменьшение или устранение остаточной мочи [21][22][23][24].…”
Section: Discussionunclassified
“…Альфаадреноблокаторы показали свою эффективность в различных аспектах коррекции нейрогенных расстройств мочевого пузыря. Так, в определенных клинических ситуациях терапия адреноблокаторами может привести к таким результатам, как уменьшение степени пузырномочеточникового рефлюкса (ПМР), улучшение со стороны императивного недержания, более редкие обострения инфекций мочевыводящих путей, выраженное улучшение уродинамических показателей, уменьшение или устранение остаточной мочи [21][22][23][24].…”
Section: Discussionunclassified
“…It has been suggested that M3 receptors on the bladder detrusor muscle might be the target of this drug (Chen et al, 2010). Through inhibiting and blocking the binding of acetylcholine to the M3 receptor, reducing the contractile force of the detrusor, and inhibiting contraction of the detrusor, solifenacin can improve the symptoms of frequent urination and urgency (Henningsohn et al, 2017). However, due to the wide distribution of M3 receptors in the body, adverse reactions such as dry mouth, blurred vision, and constipation may occur.…”
Section: Introductionmentioning
confidence: 99%